2021
DOI: 10.14740/jmc3615
|View full text |Cite
|
Sign up to set email alerts
|

Transvaginal Resection of a Rectal Gastrointestinal Stromal Tumor: A Case Report

Abstract: Gastrointestinal stromal tumors (GISTs) are a type of mesenchymal tumors. They are rare in rectum. This location is a surgical challenge due to the high morbidity after aggressive surgeries. We present the case of an 81-year-old female with a high-grade GIST treated with transvaginal excision and adjunctive therapy with imatinib. The postoperative period was uneventful without anal dysfunction. Within the types of surgical treatment available, transvaginal excision is an acceptable procedure in lesions located… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 20 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…Various surgical techniques and approaches for local resection of rGISTs have been widely described, including open transanal resection, 92 transanal endoscopic microsurgery (TEM), 93–95 transanal minimally invasive surgery (TAMIS), 96,97 laparoscopic 98,99 transperineal 100,101 presacral 102,103 transacral 104–106 and transvaginal approaches 107–109 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various surgical techniques and approaches for local resection of rGISTs have been widely described, including open transanal resection, 92 transanal endoscopic microsurgery (TEM), 93–95 transanal minimally invasive surgery (TAMIS), 96,97 laparoscopic 98,99 transperineal 100,101 presacral 102,103 transacral 104–106 and transvaginal approaches 107–109 …”
Section: Discussionmentioning
confidence: 99%
“…Various surgical techniques and approaches for local resection of rGISTs have been widely described, including open transanal resection, 92 transanal endoscopic microsurgery (TEM), [93][94][95] transanal minimally invasive surgery (TAMIS), 96,97 laparoscopic 98,99 transperineal 100,101 presacral 102,103 transacral [104][105][106] and transvaginal approaches. [107][108][109] Imatinib therapy appears to be the standard first-line treatment for locally advanced, inoperable, and metastatic patients, and for metastatic patients who have had all lesions surgically removed. 88 All GISTs have the potential to develop metastases and their biological behavior is variable.…”
Section: Prognosismentioning
confidence: 99%
“…IM, a specific tyrosine kinase receptor inhibitor (TKI), was approved by the US Food and Drug Administration (FDA) as the first-line treatment for advanced GIST in February 2002. 29 IM is also the only TKI currently available for neoadjuvant therapy (nIM), and the standard dose is 400 mg/day. 30 , 31 However, a case report also showed that sunitinib was selected for neoadjuvant therapy for gastrointestinal stromal tumors firstly.…”
Section: Treatment Of Rectal Gistsmentioning
confidence: 99%
“…IM was approved by the FDA as a first-line treatment for advanced GIST in February 2002. 29 Two-phase III trials determined that 400 mg daily was the optimal dose of IM in advanced GIST. In the trials of S0033 and phase III European Cancer Research and Treatment Group 62,005 trials, both trials demonstrated a significant clinical benefit of IM 400mg/ day.…”
Section: Treatment Of Rectal Gistsmentioning
confidence: 99%
See 1 more Smart Citation